English Teachers’ Storied Resistance and Agency vis-a-vis Neoliberal Agendas in Supranational Educational Policies in Colombia: A Narrative Study - Gómez Gaitán, Sandra Viviana; Forero Mondragón., Alber Josué; Largo Rodríguez, José David (Colombian Applied Linguistics Journal, 2023)
This article reports a narrative study on the reflexive and transformative perspectives that two English language teachers take on when they story themselves as ELT professionals.. The study adopts a narrative methodology where teachers reconstruct their meaningful professional experiences regarding the foregoing policies. In this sense, participants orally make meaning of themselves as English language professionals by reflecting on their past (retrospection), present (introspection), and future (prospection). Data was collected throughout semi-structured interviews and analyzed under a narratives framework. Findings revealed that teachers’ postgraduate education becomes a community of practice for them to problematize their past experiences with supranational language policies. Thus, such problematization allows them to exert agency through classroom micro-practices that lead them to resist oppressive education language policies. Furthermore, these micro-practices found teachers’ imagined futures and shape their identities as agents of change.